Особливості стану прооксидантно-антиоксидантної системи печінки старих щурів з різним типом ацетилювання за умов гострої нітратно-кадмієвої інтоксикації - Кметь, Т.І.; Власик, Л.І. (Актуальні проблеми транспортної медицини, 2005)
It has been established that combined nitrate-cadmium intoxication sensitivity is more pronounced in old animals with slow acetylation level and is followed by high mortality rate and more evident increase of lipoperoxidation secondary products and decrease of lactatdehydrohenesis activity.